Intraspecific demography of the silky shark (Carcharhinus falciformis): implications for fisheries management. (7th November 2019) - Grant, Michael I; Smart, Jonathan J; Rigby, Cassandra L; White, William T; Chin, Andrew; Baje, Leontine; Simpfendorfer, Colin A
Abstract: The silky shark ( Carcharhinus falciformis ) is one of the most heavily fished tropical shark species globally, and currently there is increasing concern for its conservation status. However, large differences and ambiguity in life history parameter estimates among regions complicates its conservation and fisheries management. Using a Leslie matrix model that incorporated stochastic effects, we analysed the intraspecific demography of C. falciformis using available life history data from seven regions. Among regions, large differences were observed in generation time and age-specific reproductive contributions. Carcharhinus falciformis generally had low resilience to fishing mortality ( F ) throughout its distribution. Age-at-first-capture and age-at-last-capture management approaches resulted in substantial differences among regions. This was largely influenced by age-at-maturity. However, in scrutinizing some regional life history studies, it is likely that sampling design and methodological differences among regions have resulted in inaccuracies in life history parameter estimates and subsequent demographic attributes. This implies that age and life-stage-dependent management approaches using these possibly inaccurate life history parameters may be inappropriate. We suggest that a greater emphasis needs to be placed on eliminating human sources of error in elasmobranch life history studies to ensure management for wide-ranging species, such as C. falciformis, is most effective.